2012
DOI: 10.1371/journal.pone.0052639
|View full text |Cite
|
Sign up to set email alerts
|

Self-Glycolipids Modulate Dendritic Cells Changing the Cytokine Profiles of Committed Autoreactive T Cells

Abstract: The impact of glycolipids of non-mammalian origin on autoimmune inflammation has become widely recognized. Here we report that the naturally occurring mammalian glycolipids, sulfatide and β-GalCer, affect the differentiation and the quality of antigen presentation by monocyte-derived dendritic cells (DCs). In response to sulfatide and β-GalCer, monocytes develop into immature DCs with higher expression of HLA-DR and CD86 but lower expression of CD80, CD40 and CD1a and lower production of IL-12 compared to non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…These effects were independent of CD1d, a known receptor for sulfatides, and were partially mediated by L-selectin, which was shown to bind to sulfatide in leukocytes (23). Data also point to C24-sulfatide activation of TLR4-and TLR2dependent signaling in human dendritic cells (24), while another report provides evidence that long FA chain sulfatides block LPSstimulated localization of TLR4 within lipid rafts and activation of NF-κB and MAP kinases in RAW264.7 macrophages, and prevent LPS-induced acute lethality in mice (25). Thus, the role of sulfatides in inflammation and specifically in TLR binding/activation remains poorly defined.…”
mentioning
confidence: 83%
“…These effects were independent of CD1d, a known receptor for sulfatides, and were partially mediated by L-selectin, which was shown to bind to sulfatide in leukocytes (23). Data also point to C24-sulfatide activation of TLR4-and TLR2dependent signaling in human dendritic cells (24), while another report provides evidence that long FA chain sulfatides block LPSstimulated localization of TLR4 within lipid rafts and activation of NF-κB and MAP kinases in RAW264.7 macrophages, and prevent LPS-induced acute lethality in mice (25). Thus, the role of sulfatides in inflammation and specifically in TLR binding/activation remains poorly defined.…”
mentioning
confidence: 83%
“…LDL and HDL bind the lipid metabolite βGlcCer (65,66). Lipid metabolites regulate DC differentiation/function (26)(27)(28)(29), and DCs mediate initiation of allergic disease (4,12). It is reported that βGalCer is required for hematopoiesis (67) and that ceramide is elevated in allergic non-pregnant female mice (68).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of some lipid metabolites are altered during allergic inflammation in humans and mice (20)(21)(22)(23)(24)(25). Lipid metabolites regulate DC differentiation/function (26)(27)(28)(29) and DCs mediate initiation of allergic disease (4,12). Furthermore, maternal lipids (30)(31)(32) are also present in milk and may regulate development of the immune system in the neonate.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal PM 2.5 air pollutant exposure referred to period averages from measures taken from each trimester on the basis of temporally and spatially resolved, aerosolized optical depth data. 37 For consistency, these variables were also included in multivariable models with the FVC percent predicted outcome. All models with child 3-year tocopherols were also adjusted for some hemolysis, which occurred in 22% of the samples because lipids are released from cell membranes during hemolysis.…”
Section: Discussionmentioning
confidence: 99%